Application of Shannon and Simpson Diversity Index to Study Plant biodiversity on Coastal Rocky Ridges Habitats with Reference to Census Data in the Ras El-Hekma and Omayed Area on the Western Coastal Region of Egypt - sharashy, omar (Journal of Pure & Applied Sciences, 2022)
Biodiversity is a word recently introduced by experts in field of biology, and it is important for ecosystem health and productivity, biodiversity is one of the primary interests of ecologists, and the widely used diversity indices are Shannon’s and Simpson’s index. This study aims to characterize the plant communities and to identify and compare the plant species diversity in the Ras El-Hekma area and Omayed protectorate. The results of the application of the indices of plant biodiversity in both the Ras El-Hekma area and the Omayed protectorate showed that the value of the Shannon index ( H' ) 2.058 and 2. 322, the value of the Simpson index ( D ) 0.85 and 0.92, the value of the Evenness index ( E ) 0.89 and 0.96, the value of Effective Number of Species ( ENSSh , ENSSi ) 6.66, 7.83 and 12.5, 10.19 respectively. The results demonstrated the highest values were recorded in the community of Omayed protectorate compared with the Ras El-Hekma area. The results also revealed that ( H' ) in the two communities 2 ≥ H' < 3. According to the criteria of diversity index, they were moderate diversity. As for the Evenness index (E), 0.75 >E ≤ 1. According to the categorized of the Evenness index, both are stable community. Through the results, diversity indices indicate that there is a more diverse community in the Omayed protectorate compared with the Ras El-Hekma area. The reason may be due to the individuals in Omayed was more evenly distributed among the species than the individuals in Ras El-Hekma. Based on the interpretation of the criteria and categories of Shannon, Simpson, Evenness and Effective Number of Species indices, this meant that the Omayed had high environmental wellness and biodiversity level. Both indices are more reflective in nature and can predict the ecosystem health. Therefore, it may be good to have one of these biodiversity indices to be used for plant communities to understand the ecosystem healthiness in the habitats.